Analgesic effects of oral Yokukansan on acute postoperative pain and involvement of the serotonin nervous system: a mouse model study - Shuichiro Kurita; Mika Sasaki; Moegi Tanaka; Yoshinori Kuwabara; Yukino Ogasawara; Hiroshi Baba; Yoshinori Kamiya (BMC, 2024)
Abstract Background Yokukansan, a traditional Japanese medicine (Kampo), has been widely used to treat neurosis, dementia, and chronic pain. Previous in vitro studies have suggested that Yokukansan acts as a partial agonist of the 5-HT1A receptor, resulting in amelioration of chronic pain through inhibition of nociceptive neuronal activity. However, its effectiveness for treating postoperative pain remains unknown, although its analgesic mechanism of action has been suggested to involve serotonin and glutamatergic neurotransmission. This study aimed to investigate the effect of Yokukansan on postoperative pain in an animal model. Methods A mouse model of postoperative pain was created by plantar incision, and Yokukansan was administered orally the day after paw incision. Pain thresholds for mechanical and heat stimuli were examined in a behavioral experiment. In addition, to clarify the involvement of the serotonergic nervous system, we examined the analgesic effects of Yokukansan in mice that were serotonin-depleted by para-chlorophenylalanine (PCPA) treatment and intrathecal administration of NAN-190, 5-HT1A receptor antagonist. Results Orally administered Yokukansan increased the pain threshold dose-dependent in postoperative pain model mice. Pretreatment of para-chlorophenylalanine dramatically suppressed serotonin immunoreactivity in the spinal dorsal horn without changing the pain threshold after the paw incision. The analgesic effect of Yokukansan tended to be attenuated by para-chlorophenylalanine pretreatment and significantly attenuated by intrathecal administration of 2.5 µg of NAN-190 compared to that in postoperative pain model mice without para-chlorophenylalanine treatment and NAN-190 administration. Conclusion This study demonstrated that oral administration of Yokukansan has acute analgesic effects in postoperative pain model mice. Behavioral experiments using serotonin-depleted mice and mice intrathecally administered with a 5-HT1A receptor antagonist suggested that Yokukansan acts as an agonist at the 5-HT1A receptor, one of the serotonin receptors, to produce analgesia.